A New Antioxidant Active Film Based on HDPE and Peppermint Essential Oil for Packaging Soybean Oil. (1st March 2016) - Fayaz Dastgerdi, Goly; Goli, Sayed Amir Hossein; Kadivar, Mahdi
Abstract: In this research, the effect of antioxidant active package was studied on oxidative stability of soybean oil at 40 °C during 2‐month storage. A synthetic antioxidant [Butylatedhydroxytoluene (BHT), 200 ppm] and peppermint essential oil (200 and 400 ppm) were added to antioxidant free soybean oil. To prepare active packages, the oil was filled in antioxidant active high‐density polyethylene (HDPE) bottles containing synthetic antioxidant (3700 ppm) and the essential oil (3700 and 8400 ppm). Regarding peroxide and thiobarbituric acid values, the essential oil added to the oil delayed the oil oxidation more than BHT. In active packages, the synthetic and natural antioxidants migrated from the package to the oil (with 68 and 100 % migration rate, respectively) and retarded its oxidation over the storage time. However, no significant difference was observed between essential oil and BHT in antioxidant capacity for active packages. This study demonstrated that active packages containing antioxidants could be introduced as a good replacement for direct addition of synthetic antioxidants to the oil.